Clinical profile, diagnosis and treatment of pediatric urolithiasis: a single center experience in Kazakhstan - Sagymbayeva, Assel (Bangladesh Journal of Medical Science, 2023)
Objective: The aim of our study to present the results of the clinical profile, diagnosis and treatment of children with urolithiasis in the Pediatric Urology Department of the Scientific center of Pediatria and Pediatric surgery in Almaty, Kazakhstan. Materials and methods: A retrospective data from pediatric patients with urolithiasis admitted from January 2015 to December 2021. The data was obtained from medical records and included those with diagnosis confirmed by imaging and laboratory test, as 24-hour urine exams corrected for creatinine, stone composition. Results: We reviewed 204 children with urolithiasis. The male‐to‐female ratio was 1.34:1. Congenital anomalies of the urinary tract were found in 40 patients (19.6%).Urolithiasis was more common in adolescent girls, whereas in boys the frequency of observation is higher between 11 and 17 years old (p = 0.006). Majority of the patients were from southern regions (51%) in our country. Renal colic, urinary tract infection and macroscopic hematuria were the most common clinical manifestations. Urinary tract infection was diagnosed in 185 patients (90.6%). The most frequent metabolic disorders were hypercalciuria, hyperoxaluria. In 35% of cases there was a metabolic disorder and appropriate therapy was prescribed. In the remaining cases, surgical treatment was used. Conclusion: In this study we presented the prevalence of urolithiasis in the pediatric population in different regions of our country. We identified a high prevalence of infective stone as an etiological factor of pediatric urolithiasis. Clinical symptoms depending on the age and location of the stones. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 297-304